Concern with COVID-19 pandemic threat and attitudes towards immigrants: the mediating eﬀect of the desire for tightness - Mula, Silvana; Di Santo, Daniela; Resta, Elena; Bakhtiari, Farin; Baldner, Conrad; Molinario, Erica; Pierro, Antonio; Gelfand, Michele, J.; Denison, Emmy; Agostini, Maximilian; Belanger, Jocelyn J; Gutzkow, Ben; et al. (Elsevier B.V., 2022)
Tightening social norms is thought to be adaptive for dealing with collective threat yet it may have nega- tive consequences for increasing prejudice. The present research investigated the role of desire for cultural tightness, triggered by the COVID-19 pandemic, in increasing negative attitudes towards immigrants. We used participant-level data from 41 countries ( N = 55,015) collected as part of the PsyCorona project, a cross- national longitudinal study on responses to COVID-19. Our predictions were tested through multilevel and SEM models, treating participants as nested within countries. Results showed that people’s concern with COVID- 19 threat was related to greater desire for tightness which, in turn, was linked to more negative attitudes towards immigrants. These ﬁndings were followed up with a longitudinal model ( N = 2,349) which also showed that people’s heightened concern with COVID-19 in an earlier stage of the pandemic was associated with an increase in their desire for tightness and negative attitudes towards immigrants later in time. Our ﬁndings oﬀer insight into the trade-oﬀs that tightening social norms under collective threat has for human groups.